2018
DOI: 10.1021/acsnano.8b06206
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Unilamellar Cation-Deficient Metal Oxide Nanosheet Superlattices for High-Rate Sodium Ion Energy Storage

Abstract: Cation-deficient two-dimensional (2D) materials, especially atomically thin nanosheets, are highly promising electrode materials for electrochemical energy storage that undergo metal ion insertion reactions, yet they have rarely been achieved thus far. Here, we report a Tideficient 2D unilamellar lepidocrocite-type titanium oxide (Ti 0.87 O 2 ) nanosheet superlattice for sodium storage. The superlattice composed of alternately restacked defective Ti 0.87 O 2 and nitrogen-doped graphene monolayers exhibits an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 58 publications
3
96
0
Order By: Relevance
“…During charging and discharging, sodium ions can be reversibly inserted into the Ti vacancies and interlaminar space of the superlattice. The multilayer structure without phase transition or structural change is maintained in the process of sodiation/desodiation, thus achieving excellent electrochemical performance (Figure b) . Compared with monovalent lithium ions or sodium ions, Ma et al reported that reversible Mg 2+ and Al 3+ were inserted into anatase TiO 2 , introducing a large number of Ti vacancies as insertion sites .…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…During charging and discharging, sodium ions can be reversibly inserted into the Ti vacancies and interlaminar space of the superlattice. The multilayer structure without phase transition or structural change is maintained in the process of sodiation/desodiation, thus achieving excellent electrochemical performance (Figure b) . Compared with monovalent lithium ions or sodium ions, Ma et al reported that reversible Mg 2+ and Al 3+ were inserted into anatase TiO 2 , introducing a large number of Ti vacancies as insertion sites .…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…b) Schematic illustration of the Ti 0.87 O 2 /N‐doped graphene superlattice and the capacity retentions at different temperatures. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…Copyright 2017, AAAS. 2018) Reproduced with permission . Copyright 2018, American Chemistry Society.…”
Section: Synthesis Of 2d Superlatticesmentioning
confidence: 99%
“…A post‐calcination treatment is further introduced after the flocculation for well‐integrated superlattices with intimate interactions. Recently, a Ti 0.87 O 2 /N‐doped graphene superlattice has been reported through the calcination of superlattice of electrostatically re‐stacked Ti 0.87 O 2 and PDDA‐graphene nanosheets . A possible TiOC bonding is formed during the calcination treatment.…”
Section: Synthesis Of 2d Superlatticesmentioning
confidence: 99%
“…Ty pical strategies for fabricating 2D superstructures involve arduous exfoliation of bulk precursors into monolayer, subsequently,l ayer-by-layer restacking,w hich are restricted to layered bulks,a nd in particular,t hose based on van der Waals 2D interactions,w ith low throughput and limited reproducibility. [6,7] Nevertheless,2 Ds uperlattices based on non-layer structured nanomaterials have been hardly reported. Besides,t he synthesized 2D superlattices are still subjected to irreversible aggregation during synthetic and electrode fabrication processes.…”
mentioning
confidence: 99%